Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20123110
|View full text |Cite
|
Sign up to set email alerts
|

High-Fish Oil and High-Lard Diets Differently Affect Testicular Antioxidant Defense and Mitochondrial Fusion/Fission Balance in Male Wistar Rats: Potential Protective Effect of ω3 Polyunsaturated Fatty Acids Targeting Mitochondria Dynamics

Abstract: High-fat diets rich in fish oil (HFO diet, mainly ω3-PUFAs), in contrast to high-fat diets rich in lard (HL diet, mainly saturated fatty acids) have been shown to induce improvement in mitochondrial function and fusion processes associated with a reduction in reactive oxygen species production in both liver and skeletal muscle. High-fat diets may also impair testicular function, and mitochondria represent important cellular organelles with a pivotal role in reproductive function. Mitochondria are dynamic organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The balance between fusion and fission processes produces a mitochondrial network reorganization in response to various mitochondrial stressors and diseases [49]. Among others, our previous finding evidenced a possible role of mitochondrial dynamics in the control of cellular health and functionality in different tissues [55,80], suggesting the importance of studying these physiological mechanisms, mainly in the liver, that play a key role in lipid metabolism as well as in detoxification processes against external toxic agents [81]. We chose to analyze MFN2 because it has also been suggested that MFN2 is a protective target in the liver, as it controls the physiological balance between apoptosis and autophagy in liver failure [82].…”
Section: Discussionmentioning
confidence: 91%
“…The balance between fusion and fission processes produces a mitochondrial network reorganization in response to various mitochondrial stressors and diseases [49]. Among others, our previous finding evidenced a possible role of mitochondrial dynamics in the control of cellular health and functionality in different tissues [55,80], suggesting the importance of studying these physiological mechanisms, mainly in the liver, that play a key role in lipid metabolism as well as in detoxification processes against external toxic agents [81]. We chose to analyze MFN2 because it has also been suggested that MFN2 is a protective target in the liver, as it controls the physiological balance between apoptosis and autophagy in liver failure [82].…”
Section: Discussionmentioning
confidence: 91%
“…Several research groups, including our group, have shown that HFD induces alterations in the serum lipid profile, as well as increasing both the body weight and lipid depots in adipose tissue and ectopic sites [17,29,60,61]. It is noteworthy that a high dietary fat intake has been shown to be associated with oxidative stress induction in different experimental models and tissues [29,31,32,62,63], suggesting that fatty acids represent a critical point in the development of metabolic disorders associated with obesity. Moreover, as stated above, another environmental condition that may induce oxidative stress in different tissues and organs is the exposure to environmental pollutants [15,16].…”
Section: Mitochondria and Oxidative Stress Generation In Biologicamentioning
confidence: 99%
“…DOX‐induced cellular dysfunction is associated with disrupted balance between mitochondrial fusion and fission mechanisms that are essential for health of cell and mitochondrial function (Marechal et al., 2011). MFN2, the fusion protein, is essential for the maintenance of spermatogonial differentiation and spermatogenesis (Migliaccio et al., 2019). It has been demonstrated that ROS production increased in MFN2 deficiency (Munoz et al., 2013).…”
Section: Discussionmentioning
confidence: 99%